Absolute dosimetry through radiochromic film in gamma irradiation system using a spectrophotometer UV-VIS - Vargas-Segura, Walter (2020)
The propose of this work was the Gafchromic HD-V2 film calibration, though adapting film calibration procedures applied in low dose. The films were irradiated in 11 dose values within of the range from 0 to 106,28 Gy in a gamma irradiation system, and using a spectrophotometer for the optical density measure. The absorbance spectrum were obtained for several dose, and the maximum absorbance peak was located in the wavelength of 677 nm. This wavelength was used for make the measurements of the optical density (OD), and these results were used for make the dose versus net optical density (ODn) graph. The calibration curve of the films and uncertainty in the dose were obtained, with values under 4% in dose between 10 to 20 Gy, and uncertainties under 3% for dose up from 20 Gy until complete the range of the curve. The calibration of the radiochromic film-spectrophotometer system was obtained for dose range and gamma irradiation system employed.